(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The aim of this research is to describe the Moral Message of the Pogogutat Motolu Adi’ Tradition and the Implications for Character Learning in the Young Generation of Bolaang Mongondow. The method used in this research is a descriptive qualitative method. The data sources for this research are Bolaang Mongondow traditional figures, Bolaang Mongondow cultural figures, Indonesian language teachers and observers. To collect data the techniques used were observation, interviews and documentation. To analyze the data, the methods used are study and data organization, classification and interpretation. The research results show that: 1. The moral messages contained in the pogogutat tradition are: a. Binding people to work together because the essence of humans are social creatures, as social creatures, they need the help of other people in all aspects of their lives. b. Teaching people to live, helping people in their lives, there will be ups and downs, and so on. c. Lighten other people’s burdens, d. As a form of loving each other, caring for each other, doing good to each other, reminding each other that people in big cities generally no longer show neighborly life, 2. The implications of the pogogutat tradition in forming the character of the younger generation , especially students in schools, are: The pogogutat tradition can shape attitudes and character work together to help each other, do good to each other, remind each other and love each other.